'Stuck like glue': assessing variability in hafting adhesives in the southern African Later Stone Age - Veall, MA (2019)
The characterisation of hafting adhesives, the glue of composite tools, by chemical analysis and microscopy provides a means by which we may evaluate these plastic components of technologies; reliable systems that have allowed members of our species to exist in dynamic environments and exploit a variety of resources. In southern Africa, the well-preserved assemblages of the Later Stone Age present a unique opportunity to evaluate the raw material sources of these adhesives. This thesis highlights the findings of the first multi-site study of hafting adhesives from the Holocene assemblages. The results a multi-method microscopic and chemical analysis suggest there is evidence to support variations in adhesive sources between ecological biomes and through time, with a dominance in compound adhesives found at the case study sites. The analyses of material from Sehonghong (Lesotho, Grassland) suggests a transition to the use of non-local adhesive materials among the last hunter-gatherer populations of the site. Evidence from Melkhoutboom in the Thicket Biome highlights the longstanding use of conifer pitch throughout the Holocene, while isolated hafted implements recovered from coastal caves further west along the southernmost coastline indicate a continued use of the same manufactured product into the Forest biome. From the Late Holocene assemblages at Boomplaas and Renbaan in the Fynbos, we see a diversification of resources; latex exudates from the Euphorbia and Ammocharis genus were identified at Boomplaas, while a hitherto unknown composite adhesive recipe composed predominantly of animal products and inorganic minerals was found at the Oliphant’s River valley site of Renbaan. The current and novel adhesive recipes identified within these datasets highlights the inherent value of the adhesive components themselves and provides insight into the nature of these plastic technologies, the narrative of adhesive manufacture in southern Africa, and current archaeological discussion in this region.